Assessment of knowledge and practice of oral health among nursing and pharmacy students - Baruah, Chetanjit; Rabha, Alpana P.; Saikia, Hiranya (International Journal Of Community Medicine And Public Health, 2020)
Background: Oral health is an integral part of general health and wellbeing of an individual at every stage of life. Good oral health knowledge is a requisite criterion for good oral health related behavior. So, this study was done to assess knowledge and practice about oral health and whether there is any difference of knowledge and practice about it among nursing and pharmacy students. Methods: A cross sectional study was done among 110 nursing and 90 pharmacy students in June 2019 by stratified random sampling method using a self-administered predesigned structured questionnaire. Descriptive statistics and chi-square test were applied using SPSS software. Results: Knowledge and practice of pharmacy students was found to be better than nursing students. Conclusions: Knowledge and practice of the students should be improved through health education.